Determinación toxicológica de Cocaína, Marihuana y sus metabolitos en escolares de Educación Secundaria en Lima-Perú - Anaya P., Rosalía (2000)
Percentage of Drug abuse in Peruvian population is being determined only with inquiries and no toxiccological analysis is done. For the present study, 55 National High Schools from Lima, Perú, were selected considering those with high student population. The students age fluctuated between 15 and 19 years old, and 13 301 samples were analysed. The analysis results indicated that 15.9% of students had consumed cocaine; 9.9% marijuana; 0.7% benzodiazepine; 0.3% barbiturates and no one had consumed amphetamines. At the same time of sample collection, an inquiry, was performed results but the did not agree with the ones obtained from toxicological analysis. So, we concluded, that inquiries do not demonstrate the real percentage of drug abuse, since they are not answered with responsability by fue students, may be because of fear or shame to their drug-dependence situation.